The Portrayal of the Main Character’s Trauma in As Long as the Lemon Trees Grow (2022) - Roni Nopriyanto (Passage: Journal of English Language and Literature, 2024)
Trauma has an important relation to psychology, anthropology and sociology, history, war, and more significantly, literature. This research explores the portrayal of trauma in the young adult literature novel titled As Long as the Lemon Trees Grow (2022) by Zoulfa Katouh. The novel As Long as the Lemon Trees Grow (2022) focuses on the issue of the Syrian Civil War which becomes the main reason for the main character’s trauma. By using the qualitative research method, this research aims to discover the portrayal of trauma by the main character in the narrative. Caruth’s theory of trauma (1996 is used to discover the portrayal of trauma as a response to the main character's catastrophic event in the story. The findings show two kinds of trauma symptoms that is portrayed by the main character which are hallucinations and panic attacks. However, panic attacks are not significantly explained in the Caruth’s (1996) theory of trauma. The research shows that factors such as death, loss, war, terror, and political violence caused by the government are the main reasons behind the main character’s trauma. The research significantly explores how fiction is used to understand trauma based on the main character’s behavior.